Formulasi Pengembangan Ekonomi Lokal Partisipatif Sebagai Strategi Peningkatan Daya Saing UMKM - Hartanto, Arif Dwi; Siswati, Aris; Mardiasih, Noeke Chrispur (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
This study aims to formulate the ideal PELP model as a conceptual basis for the preparation of strategies to increase the competitiveness of SMEs. This study used a descriptive evaluative method, which was carried out through field research. The research locations are in three points, namely: 1) ceramic industry center in Dinoyo, Malang City; 2) batik industry center in Celaket, Malang City; and 3) chips industry center in Poncokusumo, Malang Regency. The results of the study show that: 1) the characteristics of the majority of MSME centers are still weak in creating institutional innovations; and 2) so far, MSME centers are still categorized as not independent. Based on these problems, this study recommends five strategies, namely: 1) the need to increase the capacity of MSMEs in joint business governance; 2) optimizing the role of MSME group communication forums; 3) increasing the independence of MSMEs based on the center; 4) increasing the role of large-scale businesses in the development of MSME centers; and 5) integrated area development. These recommendations are expected to be able to become a model for strengthening the competitiveness of SMEs based on PELP.